Design and Implementation of an Online Training Course on Moodle Using the ADDIE Model: Focus on Communication Tools - Zahra, Ouariach Fatima; Amel, Nejjari; Mohamed, Khaldi (Innovations in Pedagogy and Technology, 2025)
This article presents a case study on the design and implementation of an online training course hosted on the Moodle platform, structured according to the ADDIE instructional design model (Analysis, Design, Development, and Implementation). The course was developed for second-year Master’s students in Digital Communication Strategies and aimed to strengthen their professional competencies through the integration of digital learning environments. A particular focus was placed on the use of online communication tools to enhance learner interaction, engagement, and collaboration. Four tools were employed wiki, forum, videoconferencing, and chat each serving distinct pedagogical functions and supporting either synchronous or asynchronous interaction. The design process followed an iterative approach, incorporating continuous adjustments based on feedback from course designers and early users. This case study emphasizes the central role of communication in shaping the quality of online learning and illustrates how the ADDIE model can guide the creation of interactive, accessible, and learner-centered training programs. The present article reports on the design and implementation phases, while the evaluation phase focusing on student participation, satisfaction, and pedagogical impact will be conducted and presented in a subsequent publication. The study contributes to the growing literature on Small Private Online Courses (SPOCs), Moodle-based training, and instructional design by offering practical insights into the application of the ADDIE model in professional higher education contexts.